A Retrospective Hospital Database Analysis on Substance Use‐Related Emergency Department Visits in an Ontario University‐Affiliated Hospital Setting. Issue 2 (June 2016) - Mazhar, Nadeem M.; Lau, Felix; Van Winssen, Christine; Bajaj, Neeraj; Hassan, Tariq; Munshi, Tariq; Groll, Dianne
ABSTRACT: Objectives: : We conducted a retrospective hospital database analysis to study the emergency department visits which were attributed to substance use and the associated demographic factors. Methods: : Data was gathered retrospectively from a University‐affiliated hospital database for three urban Canadian hospital emergency departments between January 1 st, 2014 and December 31st, 2014. There was a total of 2191 substance use related emergency department visits, represented by 1355 unique patients. We studied types of substances used and related factors, such as common age groups, sex, and disposition of patients. Results: : Our results indicated that the most commonly abused substances involved in emergency department visits were alcohol, multiple drug use, and cannabis. Study also found females more likely to present with stimulant use, alcohol related presentations in senior males, adolescents presenting with cannabis diagnosis and more opiate presentations in adults. Conclusions: : We suggested that further comprehensive investigations be made in order to better understand the factors related to substance use across a wide range of demographics. Abstract : Objectifs: : Nous avons réalisés une analyse rétrospective d'une base de données d'hôpital pour étudier les visites à l'urgence attribuées à la consommation de substances et les facteurs démographiques qui y sont associés. Méthodes: : Les données ont été recueillies de façon rétrospective à partir de bases de données d'hôpitaux affiliés à des universités pour trois urgences situées en milieu urbain au Canada entre le 1er janvier et le 31 décembre 2014. Un total de 2 191 visites ont été identifiées comme étant reliées à la consommation de substances représentant 1 355 patients uniques. Nous avons examiné le type de substances utilisées et les facteurs associés comme les groupes d'âge, le sexe et l'état des patients. Résultats: : Les résultats indiquent que les substances le plus souvent consommées et impliquées dans des visites à l'urgence sont l'alcool, plusieurs drogues consommées en même temps et le cannabis. Cette étude démontre également que les femmes sont plus à risque de se présenter à l'urgence sous l'effet de stimulant, les hommes plus âgés sous l'effet de l'alcool, les adolescents avec un diagnostic de cannabis et les adultes sous l'effet d'opiacés. Conclusions: : Nous suggérons que des études plus poussées soient réalisées afin de mieux comprendre les facteurs associés à la consommation de substances à travers un éventail de facteurs démographiques.